Spiral [videorecording (DVD)] : from the book of Saw - Rock, Chris; Minghella, Max, 1985-; Nichols, Marisol, 1973-; Jackson, Samuel L. (Lionsgate, 2021)
A criminal mastermind unleashes a twisted form of justice in this terrifying new chapter from the book of Saw. Working in the shadow of his father, an esteemed police veteran, brash Detective Ezekiel 'Zeke' Banks and his rookie partner take charge of a grisly investigation into murders that are eerily reminiscent of the city's gruesome past. Unwittingly entrapped in a deepening mystery, Zeke finds himself at the center of the killer's morbid game.